The combination of alkaline water provision and asthma-induced gymnastics towards peak expiratory flow rate of asthma patients at Surakarta Lung Clinic, Indonesia - Agista Delima Permadani; Mardiyono; Aris Santjaka (GHMJ (Global Health Management Journal), 2019)
Background: Asthma is an abnormality in the form of chronic airway inflammation which can be reduced by providing asthma induced gymnastics and healthy lifestyle such as consuming alkaline water.Aims: The objective of this study is to examine a combination of alkaline water provision and asthma-induced gymnastics towards peak expiratory flow rate of asthma patients at Surakarta Lung Clinic, IndonesiaMethods: This research was a quasi-experimental pre-test-post-test design with control group. The number of respondents in this study was 30 respondents, divided equally into intervention group and control group. The control group was given asthma induced gymnastics twice a week for 14 days with duration of 60 minutes, while the intervention group was provided with a combination of alkaline water pH9+ for 14 days as much as 1,200 ml/day and asthma-induced gymnastics 4 times a week for 14 days with a duration of 60 minutes.Results: There was a significant difference in the value of peak expiratory flow for 14 days in the intervention group and the control group (p < 0.001). There was an improvement in the average of peak expiratory flow rate values for each measurement in both groups, however, this study orchestrates that the intervention group has a higher improvement than the control group. The combination of alkaline water and asthma-induced gymnastics effectively and significantly improves the peak expiratory flow rate values at the Day 8 (p = 0.039) and the Day 14 (p = 0.012).Conclusion: The combination of alkaline water and asthma-induced gymnastics can be applied in nursing care management in patients with intermittent and persistent asthma. Keywords: Alkaline water, Asthma-induced exercise, Peak expiratory flow rate Asthma Received: 25 August 2018, Reviewed: 06 September 2018, Received : in revised form 23 February 2019, Accepted: 26 February 2019 DOI: 10.35898/ghmj-31550